Αpproach techniques and psychological support in pediatric patients: literature review - Anthoula Patsiala; Marianna Kerxanatzidou; Alexandra Anastasia Seirekidou (Ene, 2017)
Effective approaches and psychological support of pediatric patients provided by health professionals are complex processes. The negative reactions and fear that pediatric patients develop during their hospitalization hamper cooperation with health professionals. The pediatric nursing staff is called upon to apply appropriate techniques for managing these situations.The purpose of this paper was to investigate, through contemporary literature review, methods of technical and psychological support of pediatric patients, applied by nurses in everyday clinical practice. The management of negative reactions and fear of pediatric patients requires individualized approach, given the uniqueness of each one of them. However, there are some general measures which may bring the ultimate results. According to literature some of them are: creation of a sincere relationship through targeted discussion, application of documented interactive educational programs to familiarize with nursing and medical procedures, distraction during painful acts, such as venipuncture or bladder catheterization, and finally high perception to identify nonverbal reactions.Awareness and familiarization of health professionals with appropriate methods will improve the relationship between pediatric patients and healthcare providers.